2020
DOI: 10.18433/jpps30981
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Breast Cancer Activities of 8-Hydroxydaidzein by Targeting Breast Cancer Stem-Like Cells

Abstract: Purpose: Cancer stem cells (CSCs) play an important role in various stages of cancer development and therapy refractoriness. 8-Hydroxydaidzein (8-OHD) has revealed anti-cancer activity in different tumors. Accordingly, we aimed to assess the effects of 8-OHD on the suppression of breast cancer stem-like cells (BCSCs). Methods: The anti-proliferative and pro-apoptotic properties of 8-OHD were examined by MTS assay and flowcytometry. The expression levels of stemness markers and JAK2/STAT proteins were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The network map of MAPK and JAK/STAT-mediated apoptosis/anti-apoptosis is shown in Figure S2. It has been reported that 8-OHD triggered apoptosis in breast cancer stem-like cells (BCSCs) through blocking of the JAK/STAT signaling pathway [79]. Here, we found that JAK/STAT-related genes, SYK, STAT3, STAT5, and BIRC5, were all downregulated by 8-OHD in K562 cells, indicating that the JAK/STAT signaling pathway was attenuated.…”
Section: Analysis Of Signaling Pathways and Network Processes Using Kegg Biocarta And Metacorementioning
confidence: 62%
“…The network map of MAPK and JAK/STAT-mediated apoptosis/anti-apoptosis is shown in Figure S2. It has been reported that 8-OHD triggered apoptosis in breast cancer stem-like cells (BCSCs) through blocking of the JAK/STAT signaling pathway [79]. Here, we found that JAK/STAT-related genes, SYK, STAT3, STAT5, and BIRC5, were all downregulated by 8-OHD in K562 cells, indicating that the JAK/STAT signaling pathway was attenuated.…”
Section: Analysis Of Signaling Pathways and Network Processes Using Kegg Biocarta And Metacorementioning
confidence: 62%
“…Rajabi et al, 2020 also reported that 8-OHD triggered apoptosis in breast cancer stem-like cells through inhibiting the interleukin (IL)-6-mediated JAK2/STAT3 pathway [ 73 ]. STAT3 activation was found to be correlated with TKI resistance in CML [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that plant-derived phytochemicals have signi cant ant-cancer activities both alone or in combination with synthetic compounds [13,14]. Results of our previous investigation showed that 1-ferrocenyl-3-(4-methylsulfonylphenyl)propen-1-one (FMSP, Fig.…”
Section: Introductionmentioning
confidence: 99%